PEMBERDAYAAN PEREMPUAN MELALUI HOME INDUSTRY DAPOER KUE DAN CATERING REI’S DI RW 03 KELURAHAN BAROS KECAMATAN CIMAHI TENGAH KOTA CIMAHI - Riswani, Early Sifa; Ansori, Ansori (Comm-Edu (Community Education Journal), 2025)
Considering that poverty is a very complex problem that has an impact on the increasing needs of the community for clothing, food, and shelter which is also accompanied by an increase in population, various poverty alleviation efforts cover various aspects of community life, so they need to be implemented in an integrated manner. One way to improve the economy is to develop local businesses to improve welfare and reduce unemployment in local life. Home industry is one of the businesses carried out at home, home industry businesses can absorb unemployment and empower the surrounding community. The purpose of this study is to describe women's empowerment through the Dapoer Kue and Catering Rei's home industry. This study was conducted using a qualitative approach with a descriptive method used to find out or describe reality. Data collection used observation, documentation and interview methods. The results of the study conducted at the Dapoer Kue and Catering Rei's home industry RW 03, Baros Village, Cimahi Tengah District, Cimahi City showed that women's empowerment can improve knowledge, skills, insight, and of course increase income. The implementation stage of women's empowerment activities is related to the formulation of empowerment objectives, namely improving skills and improving the economy. Women empowerment carried out by home industry owners so that housewives can be empowered, and what the housewives feel is the same and there are other additions such as being able to gain knowledge, skills, being able to develop abilities and increase insight. Not only that, they also get income to help with daily needs. And the housewives are very enthusiastic because they also want themselves to develop.